Government transfers, COVID-19 shock, and food insecurity: Evidence from rural households in India - Kumar, Anjani; Saroj, Sunil; Mishra, Ashok K.; Rashid, Shahidur (International Food Policy Research Institute, 2022)
The COVID-19 pandemic has decimated the lives and livelihoods of people around the world. The impact of COVID-19 has been especially devastating for low-income families in rural areas of India. Food insecurity became pervasive in rural areas soon after the nationwide lockdown was announced, as many families relied on daily wage work to fund basic necessities. By providing cash transfers and the additional foodgrains, Indian policymakers acted swiftly to reduce the financial impact on family income and consumption. This paper investigates the factors affecting the participation of rural families in the cash transfer program and the effect of government cash transfers on food insecurity. Results indicate that the government cash transfer program in India decreased moderate food insecurity by 2.4% and severe food insecurity by about 0.92%.